2006
DOI: 10.1007/s00401-006-0134-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α2-macroglobulin, neutrophil elastase, and interleukin-1α differs in early-stage and late-stage atherosclerotic lesions in the arteries of the circle of Willis

Abstract: Different types of atherosclerotic (AS) lesions can be distinguished histologically and represent different stages of AS plaque development. Late-stage lesions more frequently develop complications such as plaque rupture and thrombosis with vessel occlusion than early AS lesions. To clarify whether protective, destructive, and inflammatory proteins are differentially expressed in early-stage and late-stage AS plaques we examined the proteinase inhibitor alpha(2)-macroglobulin (A2M), the neutrophil elastase (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Anti-␣ 2 -macroglobulin/AS plaque and neutrophil elastase/AS plaque did not differ among the GSTO1 genotypes, although neutrophil elastase/AS plaque was shown recently 6 to be associated with the expansion and type of AS ( Figure 1F-G).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Anti-␣ 2 -macroglobulin/AS plaque and neutrophil elastase/AS plaque did not differ among the GSTO1 genotypes, although neutrophil elastase/AS plaque was shown recently 6 to be associated with the expansion and type of AS ( Figure 1F-G).…”
Section: Resultsmentioning
confidence: 77%
“…Paraffin sections stained with anti-interleukin (IL)-1␣, anti-neutrophil elastase, and anti-␣ 2 -macroglobulin were quantitatively analyzed as described previously to determine the percentage of the AS plaque area stained with a given antibody. 6 Positive, negative, and blank controls were performed.…”
Section: Methodsmentioning
confidence: 99%
“…The target enzyme of AAT, NE, is expressed by macrophages in human atherosclerotic plaques (17), particularly within advanced atherosclerotic lesions (31). AAT might facilitate protection against matrix breakdown by NE and clearance of lipoprotein deposits.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Histological analysis of plaques from cerebral arteries has shown that the expression of neutrophil elastase is increased in late-stage plaques. 3 Epidemiological studies have shown that neutrophil counts in peripheral blood positively correlate with coronary atherosclerotic risk 4 and acute myocardial infarction risk. 5 Mouse studies reveal the accumulation of neutrophils in the luminal plaque region and adventitia of aortic plaques of mice that lack apolipoprotein E 6 and in lesions of low-density lipoprotein receptor-deficient mice.…”
mentioning
confidence: 99%